Nutrient depletion-induced production of tri-acylated glycerophospholipids in Acinetobacter radioresistens - Yu Luo (Nature Portfolio, 2018)
Abstract Bacteria inhabit a vast range of biological niches and have evolved diverse mechanisms to cope with environmental stressors. The genus Acinetobacter comprises a complex group of Gram-negative bacteria. Some of these bacteria such as A. baumannii are nosocomial pathogens. They are often resistant to multiple antibiotics and are associated with epidemic outbreaks. A. radioresistens is generally considered to be a commensal bacterium on human skin or an opportunistic pathogen. Interestingly, this species has exceptional resistance to a range of environmental challenges which contributes to its persistence in clinical environment and on human skin. We studied changes in its lipid composition induced by the onset of stationary phase. This strain produced triglycerides (TG) as well as four common phospholipids: phosphatidylethanolamine (PE), phosphatidylglycerol (PG), cardiolipin (CL) and lysocardiolipin (LCL). It also produced small amounts of acyl-phosphatidylglycerol (APG). As the bacterial growth entered the stationary phase, the lipidome switched from one dominated by PE and PG to another dominated by CL and LCL. Surprisingly, bacteria in the stationary phase produced N-acyl-phosphatidylethanolamine (NAPE) and another rare lipid we tentatively name as 1-phosphatidyl-2-acyl-glycero-3-phosphoethanolamine (PAGPE) based on tandem mass spectrometry. It is possible these tri-acylated lipids play an important role in coping with nutrient depletion.